Hidradenitis Suppurativa Online Documents Readability: An Analysis Including 23 European Languages - Skrzypczak T; Skrzypczak A; Szepietowski JC (Dove Medical Press, 2024)
Tomasz Skrzypczak,1 Anna Skrzypczak,2 Jacek C Szepietowski1 1Department of Dermatology, Venereology and Allergology, Wroclaw Medical University, Wroclaw, Poland; 2Department of Periodontology, Wroclaw Medical University, Wroclaw, PolandCorrespondence: Jacek C Szepietowski, Chair of the Department of Dermatology, Venereology and Allergology, Wroclaw Medical University, Chalubinskiego, Wroclaw, 1 50-368, Poland, Email jacek.szepietowski@umw.edu.plPurpose: Hidradenitis suppurativa (HS) is a complex disease with the vast burden to patients. The aim of the study was to evaluate readability of online electronic materials dedicated to HS.Patients and Methods: The terms "hidradenitis suppurativa" and "acne inversa" translated into 23 official European Union languages were searched with Google. For each language, first 50 results were assessed for suitability. Included materials were focused on patient's education, had no barriers and were not advertisements. If both terms generated the same results, duplicated materials were excluded from the analysis. Origin of the article was categorized into non-profit, online-shop, dermatology clinic or pharmaceutical company class. Readability was evaluated with Lix score.Results: A total of 458 articles in 22 languages were evaluated. The overall mean Lix score was 57 ± 9. This classified included articles as very hard to comprehend. Across all included languages significant differences in Lix score were revealed (P < 0.001). No significant differences across all origin categories and Lix scores were observed (all P > 0.05).Conclusion: Despite the coverage of HS on the Internet, its complexity made it hard to comprehend. Dermatologist should ensure readable, barrier-free online educational materials. With adequate Google promotion, these would be beneficial for both physicians and patients.Keywords: hidradenitis suppurativa, online education, acne inversa, readability